The prevalence of mixed genotype infections in Polish patients with hepatitis C - Ewelina Gowin; Iwona Bereszyńska; Agnieszka Adamek; Arleta Kowala-Piaskowska; Iwona Mozer-Lisewska; Jacek Wysocki; Michał Michalak; Danuta Januszkiewicz-Lewandowska (International Journal of Infectious Diseases, 2016)
Objectives: Hepatitis C virus (HCV) genotype has been described as an independent predictor of the response to therapy. A mixed infection with two types of HCV is probably an uncommon event. The aim of this study was to determine the occurrence of mixed infection with two different HCV genotypes in adult patients with chronic hepatitis C eligible for treatment. Methods: Plasma samples and clinical and demographic data were collected from 1159 patients with hepatitis C. The INNO-LiPA HCV assay was used to identify the HCV genotypes. Results: The dominant genotype was genotype 1, which was found to be responsible for 83.9% of infections, with subtype 1b being the most common. A mixed genotype infection was detected in 26 patients (2.2%). The most common mixed genotype was 1a+1b detected in 17/26 patients (65%). Antiviral therapy led to complete elimination of both genotypes in 50% of patients with 1b+3a infection and in 33% of patients with 1b+4a infection. Conclusions: The results obtained showed that infection with mixed HCV genotypes in Polish patients with hepatitis C is uncommon. The selective elimination of genotypes 3a and 4a after therapy confirms the greater resistance to treatment of genotype 1b. In the context of new anti-HCV drug development, further investigations are needed to determine the clinical importance of mixed HCV infection.